2010
DOI: 10.3109/09638288.2010.505997
|View full text |Cite
|
Sign up to set email alerts
|

Depression in acute stroke: prevalence, dominant symptoms and associated factors. A systematic literature review

Abstract: Depressive symptoms are common in the acute phase after stroke and associated with persistency of depression and mortality after 12 months. A gold standard for the measurement of depressive symptoms in relation to stroke is missing. The knowledge of PSD in the acute phase is still limited, and there is a need for continued empirical research on its profile and patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 64 publications
2
94
1
11
Order By: Relevance
“…The origin of PSD is complex and presents a multifactorial aetiology with biological and/or psychosocial components 19,20 . Some studies found a higher prevalence of PSD among women [8][9] , survivors with fewer years of education 9 and the older elderly 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The origin of PSD is complex and presents a multifactorial aetiology with biological and/or psychosocial components 19,20 . Some studies found a higher prevalence of PSD among women [8][9] , survivors with fewer years of education 9 and the older elderly 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of PSD use a variety of different rating scales to assess for depressive symptoms, and the distinction between depressive symptoms and a depressive disorder is often not clear [31]. Further, the cut-off points for defining depressive symptoms using individual scales tend to differ from study to study [31].…”
Section: Assessing Psd and Psfmentioning
confidence: 99%
“…Further, the cut-off points for defining depressive symptoms using individual scales tend to differ from study to study [31]. A meta-analysis suggests that while some of commonly used scales are helpful in screening for PSD, none are satisfactory for case finding [32].…”
Section: Assessing Psd and Psfmentioning
confidence: 99%
“…In some studies it was investigated that cognitive status and mood are more impaired than those in the same age, healthy group in the early stages of stroke (8,9). Apathy, which is a common disturbance in stroke, is defined as a lack of motivation or interest in goal-directed activities.…”
Section: Introductionmentioning
confidence: 99%